(untitled) (TAJ: Journal of Teachers Association, 2018)
Ectopic pregnancy is a common life-threating condition. Diagnosis is frequently missed and should be considered in any women in the reproductive age group presenting with abdominal pain or vaginal bleeding. This prospective observational study was conducted in RMCH to determine the incidence, risk factors, clinical presentation, treatment, morbidity and mortality associated with ectopic pregnancy. A total of 50 cases of ectopic pregnancy were operated during the study period giving the incidence of ectopic pregnancy of 8.02/1000 pregnancies. The age of the patient ranged from 18-37 years, with maximum (40%) between 26-30 years age group. 36% patients had delivered one child and 24% were nulliparous. 30% patients had pelvic inflammatory disease and 22% had history of previous abortion/ MR. All patients presented with lower abdominal pain, 68% presented with abnormal vaginal bleeding and 60% had amenorrhoea. Most of the patients were diagnosed by high clinical suspicion and confirmed by USG. 96% cases ectopic pregnancy occurred in the fallopian tube and ampullary part was mainly affected. Laparotomy followed by unilateral salphingectomy was performed in majority (60%) of cases. 22% cases ipsilateral salpingectomy with tubectomy other side and 12% cases salpingostomy were performed. The recovery of majority of patients was smooth and uneventful. There was no death in this study. TAJ 2014; 27(2): 22-26